(8/9) x (-3/4) divide (1/9) x (-4/5) divide (3/5)

1 answer

To simplify this expression, we can start by canceling out common factors in the numerators and denominators:

First, let's simplify (8/9) x (-3/4):

8/9 x -3/4 = (8 x -3)/(9 x 4) = -24/36

Next, let's simplify (1/9) x (-4/5):

1/9 x -4/5 = (1 x -4)/(9 x 5) = -4/45

Finally, let's simplify (-24/36) ÷ (-4/45):

To divide by a fraction, we multiply by its reciprocal:

(-24/36) ÷ (-4/45) = (-24/36) x (45/-4)

Now, let's simplify:

(-24/36) x (45/-4) = (24/36) x (45/4) = (1/3) x (45/4)

Again, let's simplify:

(1/3) x (45/4) = 45/12 = 15/4

Therefore, (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5) simplifies to 15/4.